Technological Aspects of Cryosublimation Fractionation of Porcine Placental Tissues - Sevastianov, Stanislav S.; Osetsky, Aleksandr I.; Goltsev, Anatoly N. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):186.